2016
DOI: 10.1177/0271678x16662891
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow in small vessel disease: A systematic review and meta-analysis

Abstract: White matter hyperintensities are frequent on neuroimaging of older people and are a key feature of cerebral small vessel disease. They are commonly attributed to chronic hypoperfusion, although whether low cerebral blood flow is cause or effect is unclear. We systematically reviewed studies that assessed cerebral blood flow in small vessel disease patients, performed meta-analysis and sensitivity analysis of potential confounders. Thirty-eight studies (n = 4006) met the inclusion criteria, including four long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
257
5
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(287 citation statements)
references
References 45 publications
23
257
5
2
Order By: Relevance
“…A pathological report has associated WMH with demyelination and axonal loss, and clinical studies have shown associations between WMH and progressive cognitive impairment and increased risk of dementia . Although previous studies reported globally reduced CBF in cerebral SVD patients with greater WMHs, the k w changes in 19 subjects with potential SVD were not significantly associated with CBF changes in this study. Subjects recruited in this study are in the early stages of WMH development (average WMH volume is 2.6 cm 3 ), and its association with k w will provide important opportunities to prevent brain damage attributed to SVD at the earliest stages and ameliorate cognitive impairment.…”
Section: Discussioncontrasting
confidence: 86%
“…A pathological report has associated WMH with demyelination and axonal loss, and clinical studies have shown associations between WMH and progressive cognitive impairment and increased risk of dementia . Although previous studies reported globally reduced CBF in cerebral SVD patients with greater WMHs, the k w changes in 19 subjects with potential SVD were not significantly associated with CBF changes in this study. Subjects recruited in this study are in the early stages of WMH development (average WMH volume is 2.6 cm 3 ), and its association with k w will provide important opportunities to prevent brain damage attributed to SVD at the earliest stages and ameliorate cognitive impairment.…”
Section: Discussioncontrasting
confidence: 86%
“…Consistent with the microstructural abnormalities, a recent meta‐analysis showed that overall cerebral blood flow was low in regions that developed WMH (Shi et al . ).…”
Section: Neuroimaging In Manmentioning
confidence: 97%
“…In a pathology study (n=15), no incomplete infarct was found in WMH 29. Though many cross-sectional studies have found low cerebral blood flow (CBF) to be associated with higher WMH burden, the causality between low CBF and WMH is unclear 35. A longitudinal study (n=575) showed that more severe baseline WMH predated CBF decline over time rather than falling CBF predating WMH progression 36.…”
Section: Introductionmentioning
confidence: 99%